Children with kawasaki disease present elevated stiffness of great arteries: Phase‐contrast MRI study. Issue 5 (29th April 2018) - Schäfer, Michal; Truong, Uyen; Ivy, D. Dunbar; Fonseca, Brian; Malone, Ladonna; DiMaria, Michael; Barker, Alex J.; Vargas, Daniel; Hunter, Kendall S.; Jone, Pei‐Ni; Browne, Lorna P.
Abstract : Background: Patients with diagnosed Kawasaki disease (KD) are known to develop extracardiac vascular lesions and are prone to accelerated stiffening of medium‐size arteries. Purpose: To noninvasively evaluate great vessel (central aorta and main pulmonary artery (MPA)) stiffness using phase‐contrast MRI (PC‐MRI). Study type: Retrospective review. Subjects: Thirty‐three patients with previously diagnosed KD and 15 control subjects underwent PC‐MRI evaluation. Field Strength/Sequence: A free‐breathing PC‐MRI sequence was applied with Cartesian encoding and retrospective sorting using a 1.5 or 3.0T system. Assessment: We evaluated regionally specific vessel stiffness using pulse‐wave velocity (PWV) and relative area change (RAC) at the ascending aorta, descending aorta, and MPA. Statistical Tests: Hemodynamics among patients with KD and controls were compared using Student's t ‐test, Wilcoxon Rank‐sum, and χ 2 . Additional group‐specific comparisons were performed using Kruskal–Wallis or one‐way analysis of variance (ANOVA). Results: Patients with KD showed elevated PWV in both ascending (5.0 ± 1.2 vs. 2.4 ± 0.5, P < 0.001) and descending aorta (4.4 ± 2.1 vs. 2.8 ± 0.8, P < 0.001). RAC was correspondingly reduced in both segments (both P < 0.01). PWV measured in MPA was increased in KD patients (2.2 ± 0.5 vs. 1.5 ± 0.6, P = 0.045) while the RAC was reduced (34 ± 6 vs. 47 ± 3, P = 0.045). There were no associations between considered vessel stiffness indices and respective ventricular size and function, functional indices, and no correlations were observed with KD severity markers. Data Conclusion: Patients with KD have elevated great vessel stiffness measured at the chronic stage of the disease. Accelerated stiffness process does not appear to affect biventricular function in youth Level of Evidence: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;47:1228–1236.